Pengembangan LKPD Berdiferensiasi Konten dengan Setting Discovery Learning pada Materi Sistem Ekskresi - Purba, Betaria Angel; Ratna Dewi, Ni Putu Sri; Heny , Ajeng Purnama (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
This development research purpose to design, analyze the validity and practicality of content differentiated student worksheets in a discovery learning setting on topic of the excretory system for grade XI senior high school students. The development model used in this study is the ADDIE model, which consists of the stages, analysis, design, development, implementation, evaluation. The implementation stage was not conducted, and the evaluation focused on formative evaluation. The study was conducted at SMAN 1 Kubutambahan. The validity test used the Gregory formula with 2 material experts and 2 media experts as respondents. Based on the experts assessment, the Gregory Validity Coefficient (GVC) reached 0,98 Indicating that the LKPD met valid criteria. The practicality test was conducted with 3 Biology teachers and 10 students of class XI SMAN 1 Kubutambahan. The practicality score by teacher was 85,9% and by students was 87,4%, both categorized as highly practical. These results indicate that the content differentiated LKPD develop using the discovery learning model for the excretory system material is very valid and highly practicalfor use in the learning process.